PENGGUNAAN PICTO TEXTUAL GLOSSES TEXT DI PONDOK PESANTREN IBNUL FALLAAH DESA BANGSAL - Komala Dwi Syaputri; Vhiska Febiola; Enny Hidajati (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
his study explores the impact of implementing Picto Textual Glosses Text in vocabulary mastery and reading comprehension among beginners at Ibnul Fallaah Islamic Boarding School in Desa Bangsal, OKI. Employing a one-group pretest-posttest design, the study involved 15 eleventh-grade students. The results revealed a slight decrease in the average post-test score (83.42) compared to the pre-test (84.25), with a significance level of 0.416, indicating no statistically meaningful difference. Nevertheless, individual student performance varied, with the highest score increasing from 95.00 to 96.25. These findings suggest that although the method shows potential in supporting individual progress, it may not yield broad learning gains within a limited intervention period. The study underscores the need for longer and more contextual implementation of visual-verbal strategies, particularly in religious educational environments where multimedia access is often limited.